Visual quickstart guide : Adobe Premiere Pro CC - Ozer, Jan, 1955- (Visual quickstart guide., 2013)
In this clear and straightforward guide, digital video veteran Jan Ozer gives beginning and intermediate video editors just what they need to know on Adobe Premiere Pro CC. Tasked-based, step-by-step instructions and loads of visuals and time-saving tips help professionals and newcomers alike quickly find and learn tasks specific to their needs, benefiting from the award-winning Visual QuickStart style. Topics covered include essential editing tasks and media-management strategies, transitions, effects and filters, rendering options, and optimal editing and production strategies for streaming delivery of HD source content. It includes coverage of all the new features in Premiere Pro CC, such as working with closed captions, enhanced multicam workflows, and significantly improved audio effects.